Modulating effect of cardiac rehabilitation on autonomic nervous system function in patients with coronary artery disease. Issue 6 (1st December 2016) - Rio, Pedro; Pereira-Da-Silva, Tiago; Abreu, Ana; Filipe, Custódia; Soares, Rui; Portugal, Guilherme; Alves, Teresa; Silva, Sofia; Mimoso, Isabel; Cruz Ferreira, Rui
Abstract : Introduction Autonomic nervous system (ANS) dysfunction is associated with prognosis in coronary artery disease (CAD). We aimed to study the cardiac rehabilitation (CR) modulating effect on autonomic function, through heart rate variability (HRV) and heart rate recovery (HRR) after exercise, in CAD patients and the associated factors. Methods This study is a retrospective analysis of CAD patients in sinus rhythm who complete a single-centre CR programme and complementary evaluation including HRV study, cardiopulmonary exercise testing, echocardiogram. Results Our sample included 142 CAD patients (85.9% male, 57.8 ± 10.2 years, 85% post-acute coronary syndrome, 15% stable CAD). There was a significant improvement in SDNN (120.7 ± 40.7 ms vs 127.6 ± 41.5 ms; P = 0.019), resting HR (71.3 ± 10.7 min–1 vs 69.0 ± 10.9 min–1; P = 0.015) and HRR (23.8 ± 12.3 min–1 vs 27.1 ± 12.5 min–1; P = 0.017) following CR. Lower erythrocyte sedimentation rate (OR 0.911; 95% confidence interval (CI) 0.838-0.989, P = 0.027), normal left ventricular (LV) function/mild LV systolic dysfunction (OR 7.879; 95% CI 2.753-17.351, P = 0.009) and SDNN lower than 100 ms (OR 9.325; 95% CI 1.775-48.978, P = 0.008) were independently associated with SDNN improvement; quit smoking (OR 4.323; 95% CI 1.136-16.454, P = 0.014) and abnormal HRR (OR 8.023; 95% CI 1.049-64.811, P = 0.035) were independently associated with HRR improvement. Conclusion The cardiac rehabilitation programme induced a positive modulation of the autonomic function in CAD patients, as reflected by SDNN and HRR improvement. This benefit was associated with ANS baseline dysfunction, lower systemic inflammation, quit smoking and normal LV function to mild left ventricular systolic dysfunction.